Prevalence of open defecation among households with toilets and associated factors in rural areas of district Sonepat in Haryana - Babita Rani; Anshu Yadav; Sanjay Kumar Jha; Anita Punia; Sanjeet Singh (Wolters Kluwer Medknow Publications, 2020)
Context: Constructing latrines and getting people to use them is one of the most effective means of improving public health and saving lives. However, building toilets alone cannot eliminate open defecation. Aims: The aim was to estimate the prevalence of open defecation and factors associated with open defecation in rural areas of a district of Haryana. Settings and Design: This community-based cross-sectional study was carried out in a rural field practice area attached to the department of community medicine of a rural medical college. Subjects and Methods: The study was carried out from July to October 2019. The data were collected from 368 randomly selected households on a pretested semi-structured proforma. Ethical approval was obtained from the institutional ethics committee. Statistical Analysis Used: The data were analyzed using the software R, version 3.6.2. Chi-square, Fisher's exact test, crude odds ratio, adjusted odds ratio with 95% confidence interval, and P value were calculated. Results: The prevalence of open defecation was 30.97% despite having a household toilet. Among the study participants practicing open defecation, the prevalence of open defecation was significantly higher among scheduled caste (64.9%), illiterates (42.7%), laborers (56.6%), and low family income (41.5%). The participants who have constructed latrine recently, i.e., <1 year before (87%), latrine constructed by government expenses (76.9%), and rarely cleaning of the latrine (76.5%) also contributed significantly. Multivariate logistic regression analysis showed that four of these predictor variables, caste, occupation of the head of the family, years since latrine constructed, and latrine cleaning remained significant predictors of open field defecation. Conclusions: Open defecation is common among latrines owners. This behavior is associated with various several structural and sociocultural factors. The present sanitation campaign should consider shifting from toilet construction to toilet use.